تأثير مستنبتات مختلفة في بعض خصائص عزلات فطر الفيوزاريوم التي تسبب ذبول وأعفان جذور غراس الحمضيات - المغربي, صباح; علاف, عصام; يوسف, تهامة (Latakia University Journal -Biological Sciences Series, 2013)
تعد مسببات ذبول وعفن جذور غراس الحمضيات Fusariumoxysporum وF. solani ممرضات متنوعة, أجريت هذه الدراسة لمعرفة تأثير مستنبتات مختلفة في الصفات المورفولوجية, التبوغ وإنتاش الأبواغ لعزلات من جنس فيوزاريوم تم الحصول عليها من بذور وبادرات حمضيات. أظهرت النتائج أن مستنبت PSA كان الأفضل لنمو مستعمرات أغلب العزلات تلاه مستنبت PDA لنمو عزلات النوع F.oxysporium, والمستنبت CDA لنمو عزلات F.solani.كما أظهرت أن أفضل تبوغ لغالبية العزلات كان على مستنبت PSA تلاه مستنبت CDA .وكان مستنبت PDA هو الأفضل لإنتاش أبواغ غالبية العزلات. Fusarium oxysporum and F. solani, causal agents of wilt and rot root in citrus seedling are variable pathogens. This study was conducted on the effect of different media in characters, sporulation, and spore germination of fusarium spp. Isolates that were isolated from seed and seedling of citrus. The data revealed that the maximum mycelial growth was obtained in most isolates on Potato Sucrose agar for F. oxysporum and F. solani, followed by Potato Dextrose agar for F. oxysporum, and by Czapek’sDox agar for F. solani. The maximum sporulation was recorded in Potato Sucrose agar medium followed byCzapek’sDox agar . The study also showed that Potato Dextrose agar was the best for germination of spores.